PEMBINAAN KARAKTER DALAM PENDIDIKAN ISLAM HOLISTIK BERBASIS PESANTREN - Ainur Rofiq; M Farid As Siddik (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
The importance of educational institutions, especially pesantren, to instill holistic character values including religious, honest, responsibility and inferiority must be appreciated by all groups. Islamic boarding schools always form their students to do good even without a qualified theory. Islamic boarding school always prints a pious and noble person. This research uses library research by gathering information and data in the form of books, journals and other scientific essays. This research results in (1) Islamic boarding school with all its limitations able to form truly intact and honest human beings (2) Islamic boarding school is able to build credible institutions (3) Integration of Islamic education and comprehensive science in Islamic boarding schools (4) Islamic boarding schools implement comprehensively holistic education.